Molecular delineation and haplotype analysis of domain membrane protein (DMP) gene influencing in-vivo haploid induction in maize - Nisrita Gain; Rashmi Chhabra; Vignesh Muthusamy; Suman Dutta; Konsam Sarika; Elangbam L. Devi; Jayanthi Madhavan; Rajkumar U. Zunjare; Aruna Kumar; Devendra K. Yadava; Firoz Hossain (Scientific Reports)
Abstract Domain membrane protein (DMP) gene is one of the key genes regulating in vivo haploid production in maize. Here, full-length sequence (931 bp) of DMP gene was sequenced in five mutant and five wild-type maize inbreds to study allelic variation. Two SNPs viz., T to C (SNP1) and G to A (SNP2) that distinguished wild-type and mutant- allele of DMP gene, converted methionine to threonine and alanine to threonine at positions 44 and 87, respectively. Two breeder-friendly PCR-based markers (DMP_SNP_TC and DMP_SNP_GA) specific to SNP1 and SNP2 were developed. These markers identified four haplotypes, viz., Hap-DMP-TG, Hap-DMP-CG, Hap-DMP-TA, and Hap-DMP-CA among a set of 48 diverse maize inbreds. Both SNP1 and SNP2 were present in DUF679_motif-2 and DUF679_motif-1, respectively and were conserved among maize and its paralogues, hence resulting in altered protein. Analysis with 11 paralogues of maize showed high similarity with DMP gene. Comparison with 11 paralogues revealed that maize DUF679 protein of DMP gene was more similar to dmp_Zm_Zm00001eb110420 paralogue. Gene structure analysis showed that most of the DMP genes have single exon. The breeder-friendly markers developed in the present study can be utilized in marker-assisted introgression of DMP gene to develop new haploid inducer lines in maize. This is the first report on identification of novel SNP differentiating the wild-type and mutant allele of DMP gene, besides comprehensive molecular characterization of the DMP gene in maize and its paralogues.